The volume regulated anion channel VRAC regulates NLRP3 inflammasome by modulating itaconate efflux and mitochondria function - Xiaoyan Wu; Xin Yi; Boxin Zhao; Yuanxing Zhi; Ziwei Xu; Ying Cao; Xiong Cao; Jianxin Pang; Ken Kin Lam Yung; Shiqing Zhang; Shuwen Liu; Pingzheng Zhou (Elsevier, 2023)
The NLRP3 inflammasome is a supramolecular complex that is linked to sterile and pathogen-dependent inflammation, and its excessive activation underlies many diseases. Ion flux disturbance and cell volume regulation are both reported to mediate NLRP3 inflammasome activation, but the underlying orchestrating signaling remains not fully elucidated. The volume-regulated anion channel (VRAC), formed by LRRC8 proteins, is an important constituent that controls cell volume by permeating chloride and organic osmolytes in response to cell swelling. We now demonstrate that Lrrc8a, the essential component of VRAC, plays a central and specific role in canonical NLRP3 inflammasome activation. Moreover, VRAC acts downstream of K+ efflux for NLRP3 stimuli that require K+ efflux. Mechanically, our data demonstrate that VRAC modulates itaconate efflux and damaged mitochondria production for NLRP3 inflammasome activation. Further in vivo experiments show mice with Lrrc8a deficiency in myeloid cells were protected from lipopolysaccharides (LPS)-induced endotoxic shock. Taken together, this work identifies VRAC as a key regulator of NLRP3 inflammasome and innate immunity by regulating mitochondrial adaption for macrophage activation and highlights VRAC as a prospective drug target for the treatment of NLRP3 inflammasome and itaconate related diseases.